The Dangers of Short-Term Confinement: Indicators of Safety Risks Among Individuals in Jail - Ellison, Jared M. (International journal of offender therapy and comparative criminology, 2024)
Guided by the premise that an individual’s safety may be more at risk when their routines, personal attributes, or lack of guardianship influence their opportunity for exposure to violence, we examined the factors that influenced victimization risks and safety perceptions among a representative sample of respondents incarcerated at a large Midwestern jail. Results showed that vulnerable individuals such as those who were victimized prior to their incarceration, and those who antagonized others such as those who perpetrated assault, were threatened more often, were more at risk of assault victimization, and perceived more dangerous conditions. Conversely, females and individuals with greater self-control were less likely to have experienced victimization and generally felt safer in jail. Our results illustrate the importance of identifying and protecting individuals who might experience greater safety risks during jail incarceration and should be interpreted alongside research and policy aimed at improving safety and welfare within correctional institutions.